PENGARUH PENDIDIKAN, JUMLAH JAM KERJA, UMUR TERHADAP UPAH TENAGA KERJA DISABILITAS DI SUMATERA BARAT - Salwa Nabila Putri; Ariusni Ariusni (Universitas Negeri Padang, 2019)
This study aims to find out determine of wages for disabled workers in Sumatera Barat. This research use cross section with 481 samples. The variables used are wage for disabled workers,education, number of hours worked, age, work experience, type of work. This research’s methods used Ordinary Least Square (OLS) Multiple linear regression analysis. This research show education, number of work, work experience had significanlly positive effect on wage for disabled workers in Sumatera Barat. Type of work has significanlly negative effect on wage for disabled worker, age had nonsignificanly positive effect on wage for disabled.